Controlled burn: the gendering of stress, burnout, and violence in modern policing - Kurtz, Don L. (Kansas State University, 2006)
Law enforcement is widely regarded as one of the most stressful and violent professions. Officer stress is associated with a number of negative behaviors and psychological outcomes including high rates of substance abuse, divorce, and violence. Concerns over officer violence include both work-related acts, like use of excessive force or unwarranted deadly force, and non-work related violence such as domestic abuse. Despite interest in the interplay between subcultural attitudes, organizational structure, and high stress events, most research on police violence fails to address a fundamental concern--that of gender. In fact, the majority of research addressing officer stress fails to mention gender or concentrates on gender as a simple control variable. In order to examine how gender, stress, and law enforcement structures predict violent behavior among police officers, this dissertation utilizes both existing data and direct officer interviews. Findings show that law enforcement remains largely a masculine enterprise, and that gender drives images, interaction, and organizational behavior, often at the expense of both men and women officers. Stress, burnout, and use of violence by officers are not simply a response to high stress events, but are embedded in the gender structure and process of policing.
Keywords: Police Stress; Gender; Sociology, Criminology and Penology (0627)